All dressed up with nowhere to go? the rapid transformation of the South African parliamentary committee system (in comparative theoretical perspective) - Calland, Richard James Tristan (Centre for Law and Society, 2026)
South Africa's transition to democracy has been a journey of almost mythical proportions. The national parliament, in Cape Town, lies at the heart of the country's new democratic dispensation. Those who were fortunate enough to be present on 9 May 1994 to see the National Assembly elect the country's first black President, Nelson Mandela, will never forget the moving spectacle that followed, as black MP after black MP was sworn into a parliament that had, for over four decades, overseen and sustained the immoral laws of the Apartheid state. Now, in theory and in practice, parliament is the institutional centrepiece of democratic governance. As such it has been transformed from a part-time, cynical rubber-stamp into a full-time, vibrant place of work. It is a transformation that however dramatic and however inspiring it has been to behold, has not been without serious problems. Over three years into the new democracy, and parliament is only just beginning to come to terms with the consequences of its transformation and many questions, both conceptual and logistical remain unanswered.